2006
DOI: 10.4161/auto.2904
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasomal and Autophagic Pathways Converge on Lipid Droplets

Abstract: Apolipoprotein B (apoB) is the primary protein of very low-density lipoproteins (VLDL). We found that apoB accumulated on the surface of cytoplasmic lipid droplets (LDs) of hepatocytes when the proteasomal or autophagic processes were suppressed. ApoB associated with LDs was poly-ubiquitinated and surrounded by autophagic vacuoles. Moreover, proteasomal subunits were concentrated around LDs. Our data suggest that apoB that is destined to be degraded remains adhered to LDs until it is broken down by the proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Out of many end products of this pathway, ubiquinone is required in the process of ATP formation during oxidative phosphorylation. Interestingly, it was reported that ubiquitinated hydrophobic proteins, which are prone to aggregation, are kept on the surface of lipid droplets (formation of lipid droplets is affected by statins20) and subjected to autophagy as well as proteasomal degradation41.…”
Section: Discussionmentioning
confidence: 99%
“…Out of many end products of this pathway, ubiquinone is required in the process of ATP formation during oxidative phosphorylation. Interestingly, it was reported that ubiquitinated hydrophobic proteins, which are prone to aggregation, are kept on the surface of lipid droplets (formation of lipid droplets is affected by statins20) and subjected to autophagy as well as proteasomal degradation41.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the importance of E3 ligases for LD turnover was reported, but further molecular components or mechanistic details are lacking (54). Apolipoprotein B accumulates in crescent-shaped structures around LDs in hepatocytes after inhibition of the proteasome or autophagy (7,55), suggesting a role of LDs in degradation of excess apolipoproteins. In support of this function of LDs, a recent study (56) demonstrated accumulation of hydroxymethylglutaryl-CoA reductase around LDs under conditions of impaired proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to the proposal that LDs might serve as an obligatory platform for the turnover of specific proteins [174]. This intermediary LD step may assist the degradation of certain highly hydrophobic proteins that would otherwise form hard-to-clear aggregates in the cytoplasm [175] or it may facilitate the wholesale delivery of a large set of damaged proteins to the lysosome via autophagy [96].…”
Section: 4 Protein Turnovermentioning
confidence: 99%